Officer-Involved: The Media Language of Police Killings - Jonathan Moreno-Medina®; Aurélie Ouss®; Patrick Bayer®; Bocar A Ba® (The Quarterly Journal of Economics, 2025)
Abstract This article examines language patterns in U.S. television news coverage of police killings. First, we document that the media use syntactic structures—such as passive voice, nominalizations, and intransitive verbs—that obscure responsibility more often in cases of police killings than in cases of civilian killings. Through an online experiment, we demonstrate the significance of these syntactic differences, revealing that participants are less likely to hold police officers morally responsible and demand penalties when exposed to obfuscatory language, particularly in cases involving unarmed victims. Further analysis of news data shows greater use of obfuscatory language when the victims are unarmed or video footage is available—situations in which obfuscation may have the greatest impact. Exploring the causes of this differential obfuscation, we do not find evidence that it is driven by either demand-side factors or supply-side factors associated with TV station ownership and political leaning. Instead, our results suggest that narratives crafted by police departments are more likely drivers of media obfuscation. This article highlights how syntactic choices and their semantic consequences in media shape perceptions, extending beyond coverage volume and bias.